1993
DOI: 10.1111/j.1749-6632.1993.tb43866.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonclassical Congenital Adrenal Hyperplasia and the Polycystic Ovarian Syndromea

Abstract: PCOS has a hormonal pattern that includes an apparent dysfunction in ovarian steroidogenesis, although the sequence (or sequences) of endocrine changes, possibly with inherent paracrine abnormalities that can establish PCOS, are only postulated. Development of PCOS in the setting of androgen overproduction (or persistent disturbances of the hypothalamic-pituitary-adrenal axis even after normalization of androgen levels) points to adrenal enzyme defects, but the precise interaction of gonad and adrenal cortex v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
7

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 52 publications
0
15
0
7
Order By: Relevance
“…Congenital adrenal hyperplasia due to 21-OHdef is a well recognized disorder among women with hirsutism and PCOS [25,26]. The prevalence of this enzymatic deficiency in women with hirsutism and PCOS varies between 1%-33%, reflecting the different criteria in the methodology of patient collection and diagnosis of the disease [9-11, 15, 17].…”
Section: Discussionmentioning
confidence: 99%
“…Congenital adrenal hyperplasia due to 21-OHdef is a well recognized disorder among women with hirsutism and PCOS [25,26]. The prevalence of this enzymatic deficiency in women with hirsutism and PCOS varies between 1%-33%, reflecting the different criteria in the methodology of patient collection and diagnosis of the disease [9-11, 15, 17].…”
Section: Discussionmentioning
confidence: 99%
“…Hirsutism, acne, menstrual abnormalities and infertility are the clinical manifestations of both disorders. In addition, sonographic abnormalities of the ovaries may be similar in women with PCOS and women with adrenal enzyme defects (29,30). Although the classical laboratory findings in PCOS are an elevated level of serum LH and an elevated LH : FSH ratio, this can also be found in LOCAH (17,31,32) and approximately 60% of patients with PCOS do not have this inappropriate gonadotropin secretion (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Dewailly et al (17) have found an elevated LH : FSH ratio in 23% of patients with LO 21-OH deficiency. In many patients with PCOS, dexamethasone treatment is associated with a frequency of ovulation, and can reverse symptoms of hyperandrogenism (5,30). The clinical feature suggesting PCOS was identified in 39% of females with diagnosis of LO 21-OH deficiency (17).…”
Section: Discussionmentioning
confidence: 99%
“…17OHP was the most frequently elevated hormone, suggesting that in addition to screening for CAH, mild increases of this hormone can be used to support PCO diagnosis in an appropriate clinical setting. Mulheres com hiperplasia congênita adrenal (HCSR) de forma não clássica também apresentam como manifestações hirsutismo, acne, irregularidade menstrual, em quadro clínico indistigüível da SOP (3,4). A forma mais comum é por deficiência da enzima 21-hidroxilase.…”
Section: Introductionunclassified